(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The paper presents a comprehensive analysis of weak anomalies identified by various geophysical methods: using statistical methods and identifying their relationships with mineralization. The data, obtained from the studies of the T’Tjujur–Chambarak copper ore deposit on the methods of magnetic prospecting, natural electric field and vertical electrical sounding, are considered in the form of a group of random variables that obey the laws of normal and lognormal rules. On the results of statistical analysis, those areas of the survey are considered as anomalies, where points are regularly accumulated, for which the detected values are most impossible for a given distribution. At the same site, the presence of weak anomalies identified by various methods makes it possible to speak with confidence about the existence of ore bodies that cause these anomalies.